The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11695-017-3035-5
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Counts and Liver Enzymes After Gastric Bypass Surgery

Abstract: BackgroundObesity is associated with chronic inflammation, liver steatosis and increased liver enzymes such as gamma-glutamyltransferase (GGT) and alanine aminotransferase (ALT), markers for non-alcoholic fatty liver disease (NAFLD) and liver fat content. Increased platelet counts (PCs) are a biomarker reflecting inflammation and the degree of fibrosis in NAFLD. We investigated alterations in PCs, GGT, ALT, C-reactive protein (CRP) and ferritin after Roux-en-Y gastric bypass (RYGBP).MethodsOne hundred twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…Platelet size and platelet count were correlated inversely, in accordance with small scale studies [ 17 ], and showed associations with BMI in opposite directions. This is in accordance with opposite changes, a reduction of platelet count and an increase in MPV, after bariatric surgery [ 50 , 51 ] and in association with liver fibrosis [ 45 , 52 ]. The association of BMI with MPV and PDW, however, was inverse only for pre-menopausal women, but was positive for post-menopausal women, as well as for men.…”
Section: Discussionsupporting
confidence: 82%
“…Platelet size and platelet count were correlated inversely, in accordance with small scale studies [ 17 ], and showed associations with BMI in opposite directions. This is in accordance with opposite changes, a reduction of platelet count and an increase in MPV, after bariatric surgery [ 50 , 51 ] and in association with liver fibrosis [ 45 , 52 ]. The association of BMI with MPV and PDW, however, was inverse only for pre-menopausal women, but was positive for post-menopausal women, as well as for men.…”
Section: Discussionsupporting
confidence: 82%
“…In our patients with obesity, we observed a significant decrease of all biochemical and metabolic parameters assayed after bariatric surgery, clearly showing that LSG was effective in improving serum cytokine and the adipocytokine profile, thus ameliorating systemic inflammatory and metabolic status [43, 44]. We noted a statistically significant reduction of platelet count, as Johansson et al [45] also showed in 124 morbidly obese non-diabetic patients 12 months after Roux-en Y gastric bypass. In our population this decrease was not evident in ob T2DM, perhaps due to a more severe inflammation state and a higher degree of fibrosis than the ob N and ob preDM subgroups, which also persisted after surgery.…”
Section: Discussionsupporting
confidence: 75%
“…However, statins raise BMI in both sexes (Table 1 ), while genetically mimicked effects on calcium and SHBG were specific to women, suggesting a more complex explanation. A trial of gastric bypass suggested that BMI increases platelet count [ 56 ] but genetically predicted BMI does not appear to affect platelet count in women (Additional file 1 : Table S14). However, BMI is well-known to play a crucial role in BMR in both sexes [ 57 ].…”
Section: Discussionmentioning
confidence: 99%